Impact of Freshwater Inflow From the Volturno River on Coastal Circulation - Sorgente, Roberto; Di Maio, Antonia; Pessini, Federica; Ribotti, Alberto; Bonomo, Sergio; Perilli, Angelo; Alberico, Ines; Lirer, Fabrizio; Cascella, Antonio; Ferraro, Luciana (Frontiers in Marine Science, 2020)
The coastal area located in front of the Volturno river’s estuary (Gulf of Gaeta, central-eastern Tyrrhenian Sea) has been synoptically sampled during seven surveys, between June 2012 and October 2014. The vertical profiles of temperature and salinity have been acquired on a high resolution nearly-regular grid, in order to describe the spatial and temporal variability of the water masses characteristics. Moreover, to provide a first assessment of the steady circulation at small scale, the three-dimensional velocity field associated to each survey has been obtained through the full momentum equations of the Princeton Ocean Model. The data analysis has shown the entire water column characterized by an evident thermal cycle and a vertical thermohaline structure dominated by three types of water masses: the freshwater of river’s origin, the saltier coastal Tyrrhenian waters and transitional waters, resulting from the mixing of them. The freshwater inflow strongly affected the density distribution, causing a strong temporal variability in the upper layer. Its impact was more evident in winter inducing also a temperature inversion along the water column. In case of rainy events, its effect was clear also in condition of high vertical temperature stratification, forming a surface-trapper layer characterized by high density gradients. Together with wind forcing, they contributed to the formation of small scale shallow features, such as longshore currents, cyclonic and anticyclonic eddies. The latter influenced the vertical stratification and modify the coastal circulation preserving the transitional waters from the surrounding saltier ones.